2005
DOI: 10.2224/sbp.2005.33.8.793
|View full text |Cite
|
Sign up to set email alerts
|

Separating Gender Biases in Screening and Selecting Candidates for Hiring and Firing

Abstract: A two-stage procedure (consideration set formation and final choice) was used to track the emergence of gender biases in hiring and firing decisions. Participants were allowed to select their own strategy for narrowing choice options (which candidates to retain or which candidates to delete). Each of the two experiments included a condition where job candidates were considered for hiring and a condition where current employees were considered for firing. Candidate features varied across experiments but the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
2
6
0
1
Order By: Relevance
“…Male business students showed a gender bias in their preference for hiring male applicants in the absence of information indicating female applicants' leadership competence. Moreover, consistent with previous research (Biernat and Fuegen 2001;Levin, et al 2005), the present study demonstrated that gender bias might only operate at a distinct stage of the decision-making process, that is, at the final-choice stage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Male business students showed a gender bias in their preference for hiring male applicants in the absence of information indicating female applicants' leadership competence. Moreover, consistent with previous research (Biernat and Fuegen 2001;Levin, et al 2005), the present study demonstrated that gender bias might only operate at a distinct stage of the decision-making process, that is, at the final-choice stage.…”
Section: Discussionsupporting
confidence: 92%
“…However, the personnel selection process usually includes at least two important steps (Levin et al 2005): (1) The preliminary decision which involves an initial screening of persons from the pool of applicants, where if successful, allows applicants to be placed on the short list and (2) the subsequent decision in which an applicant/ person will be hired from the shortlist. According to Biernat and Fuegen (2001) the process of short-listing requires matching the applicant against minimum requirements for the job and the process of hiring requires matching the applicants against confirmatory requirements.…”
Section: Introductionmentioning
confidence: 99%
“…According to the shifting standards model (Biernat, Kobrynowicz, & Weber, 2003; Biernat, Manis, & Nelson, 1991), in hiring decisions more evidence of competence is required from female than male candidates to achieve the same outcome (Biernat & Kobrynowicz, 1997). Similar gender bias disadvantageous to women have been demonstrated in firing versus retention decisions (e.g., Levin, Rouwenhorst, & Trisko, 2005).…”
Section: The Content Of Gender Bias In Performance Appraisals and Persupporting
confidence: 58%
“…However, this does not imply that female dendrochronologists do not experience other types of gender bias and we do not intend to belittle the challenges that women dendrochronologists have overcome to gain the same level of recognition of their research as their male counterparts. If anything we laud the efforts of women researchers who overcome well-documented biases in hiring processes (Levin et al 2005;Schmader et al 2007), promotion decisions (Carr et al 2003;Heilman and Okimoto 2008), tenure decisions (Luzzadder-Beach and Macfarlane 2000), and grant awarding (Bornmann and Daniel 2005;Bornmann et al 2007) to achieve the same level of success as their male counterparts. …”
Section: Resultsmentioning
confidence: 99%